Vivere il presente, progettare il futuro. L’esperienza sociale della transizione professionale - Piromalli, Leonardo (Cambio. Rivista sulle Trasformazioni Sociali, 2018)
The aim of this paper is to explore the social experiences of some workers in different professional transition scenarios. I focus on observing subjective practices, precariousness and impermanences in order to grasp the tensions in individual experience and understand the meanings actors assign them. I gathered sixteen semi-structured interviews with workers in professional transition phases distributed in four different scenarios, balanced by gender. Basing on the stories collected, I discuss of an occasionally harsh tension between the experience subjects wish for themselves and the one organizational instances impose on them. Subjectivity as an assertion of originality and authenticity thus conflicts with rationalization as an incitement to efficiency and progress. Also, different spheres of experience seem to mutually interact. Employment, therefore, would be a sort of carrier for autonomy, as it would enable the subject to plan and act on other spheres of experience.